ATS ANALYSIS, DESIGN AND DEVELOPMENT OF THE ALUMNI TRACKING SYSTEM OF THE LICERIO ANTIPORDA SR. NATIONAL HIGH SCHOOL-DALAYA EXTENSION - UMOSO, CRISS MERFLOR (International Journal of Arts, Sciences and Education, 2021)
Technologically, alumni tracking system is one example software platform used to track alumni. It eliminates the need to track graduates using pen and paper or having to gather in person, the need to manually track alumni in the school. The purpose of the study was to analyze, design and develop a system a sytem that aids in improving the existing tracking strategy where all the alumni can easily access relevant informartion about LASNHS-Dalaya Extension, a portal where persistent records of all graduates can be updates including their current job status, feedback towards inproving the school processes and more. Through the software development (SDLC) methodology, the steps were carefully implemented. The problems, issues, and challenges in the tracking processes, and management of the alumni tracking were identified. The study was conducted at Licerio Antiporda Sr. National High School- Dalaya Extension.The problems and challenges include but not limited to timeliness in the provision of immediate, accurate, and reliable data of alumni; the process involved is time-consuming and requires more manpower to track alumni; issues on safety of teachers in tracking alumni. The manual processes were systematically improved with the implemented system. The system was made available online in a secured hosting facility making it accessible across different web browser and media or devices. The researcher invested in the domain and hosting registration. The site is accessible online thru www.lashnhsdalaya.org. In conclusion, the developed Alumni Tracking System is a potential technological tool in tracking instead of using the manual process. It shows that has a great impact to the learners and teachers in terms of tracking, data collection and therefore a contributing technology to the school. Hence, it is recommended to continually utilized and updated for the purposes of management program development while reflecting from the status of its alumni.